Cutaneous squamous cell carcinoma arising in hidradenitis suppurativa: A case report. (May 2019) - Roy, Catherine F; Roy, Simon F; Ghazawi, Feras M; Patocskai, Erica; Bélisle, Annie; Dépeault, Alexandra
We present a case of a 64-year-old man who presented with a rapidly growing tumor in the left buttock and intergluteal cleft area, which was affected by hidradenitis suppurativa. The patient was on tumor necrosis factor-alpha inhibitors for hidradenitis suppurativa for 2 years prior to the development of the mass. Initial biopsy of the mass showed a well-differentiated squamous cell carcinoma with spindle cells and positive epithelial immunomarkers. Subsequent excisional biopsy of the tumor showed an infiltrating poorly differentiated squamous cell carcinoma composed of islands of atypical sarcomatoid spindle cells. Squamous cell carcinoma arising in hidradenitis suppurativa is a rare complication which may occur secondary to chronic inflammation and epidermal hyperproliferation in hidradenitis suppurativa–affected areas.